Clinical characteristics and outcomes of COVID-19 infection in nine pregnant women: a report from a sub-Saharan African country, Senegal - Diouf, Abdoul Aziz; Mbaye, Khardiata Diallo; Gueye, Mamour (Pan Africa Medical Journal, 2020)
Introduction: to investigate the clinical characteristics of COVID-19 in pregnancy in Senegal. Methods: this was a cross-sectional and descriptive study of all cases of COVID-19 including nine pregnant women who were admitted in COVID-19 treatment centers in Senegal from March 2 to May 15, 2020. SARS-COV-2 infection was confirmed by PCR. Patients’ characteristics, clinical features, treatment and outcome were obtained with a customized data collection form. Results: the frequency of the association COVID-19 and pregnancy was 0.5%. The age range of the patients was 18-42 years with an average 28 years, and the range of gestational weeks at admission was 7 weeks to 32 weeks. None of the patients had underlying diseases. All the patients presented with a headache and only four of them had fever. Other symptoms were also observed: two patients had a cough, two had rhinorrhea, and two patients reported poor appetite. The median time to recovery was 13.6 days, corresponding to the number of days in hospital. None of the nine pregnant women developed severe COVID-19 pneumonia or died. Conclusion: pregnant women appear to have the same contamination predispositions and clinical features of SARS-COV-2 infection as the general population. This study shows no evidence that pregnant women are more susceptible to infection with coronavirus.
Keywords: COVID-19; SARS-COV-2; coronavirus; pregnancy; Senegal; CEA-SAMEF; Université Cheikh Anta Diop